Iloprost in Acute Post-kidney Transplant Atheroembolism: A Case Report of Two Successful Treatments - Corradetti, Valeria; Comai, Giorgia; Ravaioli, Matteo; Cuna, Vania; Aiello, Valeria; Odaldi, Federica; Angeletti, Andrea; Capelli, Irene; La Manna, Gaetano (Frontiers in Medicine, 2020)
Cholesterol embolization (CE) is a rare and fearsome post transplant complication, responsible of primary non function (PNF) or delayed graft function (DGF), whose incidence is expected to increase since the older age of donor and recipients and extended criteria donation. Therapy with statins and steroids is not of proved efficacy. Agonism of prostaglandin I2 has been reported as useful in systemic CE. We report two cases of acute post transplant CE in which iloprost (0,05 mg/kg/die) has been added to statin and steroid therapy. CE was due in the first case to embolization from the kidney artery and produced embolization in small vessels, after long DGF and 15 days of iloprost therapy renal function recovered. The second is the case of embolization from the iliac artery of the recipient where CE manifested as partial renal infarction. After 5 days of iloprost creatinine improved. Iloprost acts on vasodilation and on different pathways of inflammation improving anti-inflammatory profile. Post-transplant CE is difficult to diagnose and, if not treated, can lead to loss of function. Iloprost could help in accelerating recovery of function